An Importance of the Authentication Mechanisms in the Networks: A Literature Survey - Selvamani, D.; Selvi, V (Asian Journal of Electrical Sciences, 2018)
Security is very important for any kind of networks. As a main communication mode, the security mechanism for multicast is not only the measure to ensure secured communications, but also the precondition for other security services. Attacks are one of the biggest concerns for security professionals. Attackers usually gain access to a large number of computers by exploiting their vulnerabilities to set up attack armies. This paper presents a brief survey on the authentication mechanisms in the networks for ensuring the security in various domains.